Small but threatening: Punctate Outer Retinal Toxoplasmosis (PORT), a case series report. - Rebeca Paquentín-Jiménez; Ronald Rivera-Sempértegui; Luz Elena Concha-Del-Río (PLoS Neglected Tropical Diseases)
Aim To emphasize the importance of promptly assessment of punctate outer retinal toxoplasmosis (PORT), and to present a case series in a third-level reference center in Mexico City. Methods Retrospective, observational case series of eight eyes of eight patients who presented PORT between January 2020 to February 2023. Diagnosis was made by uveitis specialists based on clinical findings, serology, and multimodal imaging. Descriptive statistics were used to exhibit absolute and relative frequencies. Results Patient ages ranged from 19 years to 67 years old. Each patient presented creamy yellowish-white, punctate outer retinal lesions. All patients had SD-OCT showed outer retinal alterations and in autofluorescence presented hyperautofluorescent lesions. 85% of the patients improved their BCVA after treatment, but three (42.8%) were legally blind. Conclusions PORT is an atypical presentation of ocular toxoplasmosis. Lesions usually lead to retinochoroidal scarring which can significantly diminish a patient's BCVA irreversibly. Recognition of PORT lesions is important since timely and efficacious therapy leads to better visual prognosis and diminish the risk of legal blindness.